The Influence of Indigenous Peoples' Local Wisdom Values on the Understanding of Civic Education in Kampung Naga Elementary School - Diyanti, Istiqomah Eka; Rahmatika, Rosatria; Rosmilawati, Ila (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
Local wisdom that develops in indigenous peoples is a form of culture that is still sustainable and has noble values that can enrich students' understanding of civic education. However, in the context of formal education, the integration of local wisdom with the national curriculum still faces various challenges. The purpose of this study is to analyze the influence of indigenous peoples' local wisdom values on elementary school students' understanding of civic education. This study uses a quantitative method with a survey approach to analyze the influence of indigenous peoples' local wisdom values on elementary school students' understanding of civic education. The results of this study state that local wisdom values, such as mutual cooperation, deliberation, and respect for nature, have a significant influence on elementary school students' understanding of civic education. Deliberation showed the strongest influence, followed by mutual cooperation and respect for nature, all of which contributed positively to improving students' understanding of the concept of citizenship. In addition, an R-square value of 0.65 indicates that local wisdom is able to explain most of the variations in students' understanding, which emphasizes the importance of integrating local values in the learning process. This research also highlights the need for the active role of teachers and communities in connecting formal materials with students' socio-cultural contexts, as well as opening up opportunities for the development of a more inclusive and culturally relevant curriculum.